Shifting obsessions : three essays on the politics of anticorruption - Krastev, Ivan, 1965- (Central European University Press, 2004)
This book is not a study of anti-corruption policies. Instead, it looks at the politics of anti-corruption. Policies are what institutions do. But in analyzing politics, this book seeks to discover why institutions do what they do. The author delves into political motivations at a time when "combating corruption" is the fashion among the academic community. Krastev argues that anti-corruption sentiments are not driven by the actual level of corruption but by general disappointment with liberal reforms that cause rising social inequality. In this collection of essays, the author makes the provocative argument that the current corruption-focused policies are doomed